Relationship between Self-Efficacy and Student’s Achievement in Mathematics among the Senior Secondary Two School Students in Bauchi Metropolis, Bauchi State. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the relationship between mathematics self-efficacy and mathematics achievement among senior secondary school students in Bauchi Metropolis, Bauchi State, Nigeria. A correlational research design was employed. A sample of 400 Senior Secondary Two (SS2) students (180 males, 220 females) was selected using stratified random sampling from ten public secondary schools. Data were collected using a Mathematics Achievement Test (MAT) and a Mathematics Self-Efficacy Questionnaire (MSQ). Three research questions and three corresponding hypotheses were formulated and tested at a 0.05 significance level using Pearson Product Moment Correlation. The results revealed that both mathematics self-efficacy and achievement levels among students were low. A strong positive relationship was found between students' mathematics self-efficacy and their mathematics achievement (r = 0.790, p < 0.001). Gender‑specific analyses showed a moderate positive relationship for male students (r = 0.469, p < 0.001) and a strong positive relationship for female students (r = 0.688, p < 0.001). The study concludes that improving students' mathematics self‑efficacy is a viable pathway to enhancing their mathematics achievement. Recommendations include curriculum review, teacher training focused on self‑efficacy development, and targeted interventions for male students.